Constitution and Protection of Fundamental Environmental Rights in France : Challenges for Thailand - tirasangka, tannapar (King Prajadhipok’s Institute Journal, 2020)
This article acquired from a research project titled “Constitution and Protection of Fundamental Environmental Rights in France : Challenges of Thailand”. The project presented to “Direk Chaina” research Center, the faculty of Political Science, Thammasart University. It addresses questions on how to make fundamental environmental rights concrete reality in Thailand and how to manage its natural resources, which is its public national treasure, to maximize utility with sustainability. It approaches such questions through foundational knowledge relevant to fundamental environmental rights which are written in other countries’ as well as in Thailand’s constitution : what aspects are included, what are conceptual principles and scopes of such rights? The approach is employed to assure concrete reality of people’s fundamental rights and liberty as well as to provide applicable insights for any agencies including for court trials in related cases. Using qualitative methods and in-depth interview with persons related to the issues on environmental rights, it argues for (1) broader and more concrete provision of environmental rights in the constitution along with support for better awareness and acknowledgement of environmental rights in the society, that is, the governmental sector should employ a principle of social process, (2) making a law code on natural resources and environment to integrate legal enforcement of related agencies, (3) bringing about realistic enforcement of fundamental environmental rights through policies of government and related agencies, (4) establish a process for strong assurance of environmental rights through checking operated by courts and judicial process.